Conservation Management : Study Of Turtle Conservation Pangumbahan Beach, Sukabumi - Muhammad Haikal Fahmi (International Journal of Ecophysiology, 2022)
This article review Conservation Management research: Pangumbahan Beach Turtle Conservation Study, Sukabumi Regency. In this article, author discusses the conservation of the Green Turtle (Chelonia mydas). and a conservation area management system that refers to: Sustainable turtle conservation, an ecotourism-based conservation system and sustainable turtle habitat management on Pangumbahan beach, Sukabumi Regency